Dynamics of Prey-Predator Interaction with Type II Holling Response Function, Additional Food, and Anti-Predator Behavior - Aufaniyah, Nafa Lingga; Abadi, Abadi (MATHunesa: Jurnal Ilmiah Matematika, 2023)
This study discusses the interaction model of prey-predator in the presence of additional food and the ability of anti-predator behavior on prey using the type II Holling response function. This research is carried out starting from the study of the literature, contructing models, determining equilibrium points, analyzing equilibrium points, numerical simulation, and drawing conclusion. From the results of the model analysis, four equilibrium points were obtained, namely the extinction of the two unstable populations, the extinction of predators, and two points with the existence of both stable populations with conditions. Based on the results of the analysis carried out, there is a change in the system solution from the limit point which is the boundary point and , then it is continued to the right to produce two point solutions, namely, point is stable to the Hopf bifurcation point when A = 0.239884 and is unstable until A = 0.147059. after the hopf bifurcation there is a change in stability to become unstable which coincides with a stable limit cycle. The simulation results show that additional food affects the stability of prey and predators even though there is anti-predator behavior on prey.